Analysis of the Role of Policy Socialization, Asset Management, and Performance Management in Improving the Effectiveness of Public Services in West Java - Judijanto, Loso; Lesmana, Tera; Zulfikri, Agung (West Science Social and Humanities Studies, 2024)
This research paper investigates the role of policy socialization, asset management, and performance management in enhancing the effectiveness of public services in West Java, Indonesia. Through a quantitative analysis, data was collected from public service providers and users in the region using structured surveys. Statistical techniques including regression analysis and correlation analysis were employed to analyze the data. The findings revealed significant positive correlations between policy socialization, asset management, performance management, and public service effectiveness. Regression analysis further demonstrated that these variables were significant predictors of public service effectiveness, with performance management exhibiting the strongest predictive power. These results underscore the importance of integrated governance approaches in optimizing public service delivery and promoting socio-economic development in West Java.